An Identification Key to Antarctic Fish leeches (Hirudinea: Piscicolidae) - Utevsky, A.Yu. (Український антарктичний журнал, 2005)
The revised list of Antarctic fish leeches (Hirudinea: Piscicolidae) is presented. It includes 21 species belonging to 13 genera. The article contains identification keys to subfamilies, genera and species, short descriptions, information on hosts and geographical distribution of leeches and images of 20 species.